Drawings and monotypes - O'Donnell, Mark A., author; Ellerby, David A., advisor; Lakin, Barbara L., committee member; Orman, Jack L., committee member; Cartwright, Corey, committee member (Colorado State University. Libraries, 1992)
THE DRAWINGS: My drawings make clearer, through the process, an easily over complicated message. Recently I have discovered that at the heart of my work all along was my obsession with a single form or shape. Often these forms and shapes are suggested by my dreams. The work is very much about its own existence. That is more than an attempt to recreate the image in my mind's eye. I view that mind's image only as a starting point. Nor are these drawings about controlling or intellectually organizing those shapes. Instead I have learned to appreciate them in a more naturalistic environment. The marks, shapes, forms and colors exist in the nature of the dream. Even when I start with the dream as the subject for a work, the successful drawing takes on a life of it's own. I find myself instinctively associating most of the forms to the human figure as I am most drawn to shapes of a natural, organic, or figurative construction. Often the color is suggested by the dream image but most often evolves in the drawing. The extreme surface activity in the drawings results from the difficult translation of the multidimensional dream image to a two dimensional drawing. In the dream I perceive things in many dimensions. I sense that I can move around a shape which may appear flat or three dimensional. My mind moves over or through an object and it is this multidimensional environment of the dream that I visualize when drawing. The many layers of the drawings relate to this awareness of many dimensions. It is when the drawings and the subconscious dream-like images feed off of one another that I feel most in tune with the work. These works rely greatly on the aggressive marks and elaborate surface activities to mirror the sensation of the other-worldly atmosphere of the dream. Although my drawings are the collaboration of many individual marks, these marks do more than just make up the whole of the image. They are more than mere parts of the shapes and forms of the drawings. I have also been involved with monotype and many of the same sensibilities have influenced my drawings. In the drawings I start by building up many layers of wax crayon, raw wax, dry pastel and other ground pigments which are burnished into the layers below. During this initial layering process the drawing goes through many transformations. When I later scrape through the many layers of what are by then different drawings, I recognize marks shapes and surfaces which remind me of the dream-like environment. I am in a sense excavating the layers to construct the drawings. This surface removal process is very similar to the selective wiping technique of the monotypes. THE MONOTYPES: As explained above, the monotype is a process of discovery. There is something very peaceful and methodical about rolling the plate black with ink and staring into the black rectangle until I discover an image. When I don't immediately discover an image in the ink, I start by making random wipes at the plate until those marks suggest something. Once I reveal an image the wiping becomes more selective as I manipulate the plate. The images I find in the mono types are usually figurative but not always. Sometimes the drawing in the ink takes on a life of its own and often the original image is lost or forgotten. I try to use materials in all of my work which lend themselves to discovering an image within the surface. Sometimes I approach the plate with a specific image in mind but only when I allow that image to be changed by the process does the finished work exude life. By that I mean that I work and manipulate the plate with a certain degree of mechanical knowledge about what a specific line, technique or tool will do, but when things are really working, it's as though I'm wiping away a veil of ink to discover an image below that was there before I began. Dreams have always been a source for my drawings and not all of my dreams are horrible experiences but often it is the darker images which stay with me and move me the most. The drawings and monotypes are a map of a not so distant memory. The record of a journey of searching. A search for the combination of marks, shapes and colors which most closely depict the striking reality of the dream. Always in the dream there is a dominant shape which grounds me in nature.
Keywords: Drawing -- Themes, motives; Drawing -- Technique